General Awareness and Knowledge about Glaucoma Cataracts for Diabetic - Banawan Hassan Al-Kanany, Nawar; EMAD KADHIM, LUBNA (International Journal of Engineering and Technology, 2018)
Horizontals and verticals cups to discs percentages are the most crucial limitations used clinically to find glaucoma or observer its growth and are physically calculated from pictures of retinal fundus of the optic nerves heads. Appointed to the rarity of the glaucoma specialists as well as the rising of glaucoma’s population, an automatically analyzed horizontal and vertical cup to disc ratios (HCDRs and VCDRs, resp.) may be valuable for glaucoma monitoring. We description one algorithm to determine the HCDRs and VCDRs. This algorithms, amount and pictures techniques were technologically advanced for segmenting the disc, though thresholding operating Type-II fuzzy method was progressed for slices of the cup. The outcomes from the algorithms were confirmed using the guide of images markings from a dataset of glaucomatous images (retinal fundus images for glaucoma analysis (RIGA dataset)) by five ophthalmologists. The algorithm’s accuracy for HCDRs and VCDRs merged was 65.3 %. Simply the accuracy of guide markings by one ophthalmologist was higher than the algorithm’s accuracy. The algorithm’s best understanding was with markings by ophthalmologist number 1 in 130 images (32.7%) of the whole examined images. Flow chart for images analyzed were  add in this paper as reference.